2023
DOI: 10.6007/ijarafms/v13-i1/16574
|View full text |Cite
|
Sign up to set email alerts
|

Examining The Value Relevance of Biological Assets and Their Fair Value Change in Malaysia

Abstract: The Malaysian Financial Reporting Standard 141 (MFRS 141) on agriculture requires all agriculture companies to measure their biological assets based on fair value less cost to sell. Some researchers argue that fair values of biological assets are not reliable and relevant whereas the others suggest that they are value relevant. The purpose of this study is to investigate the value relevance of biological assets and the change in the fair value of biological assets in Malaysia, as measured in accordance with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…In the present research, BIO and FIV are calculated in the same year. It is in line with previous research IOP Publishing doi:10.1088/1755-1315/1297/1/012069 7 [8], [16], [19], [22]. In Alfarisyi et al [15], the BIO from the previous year matches the FIV this year.…”
Section: Hypotheses Testingsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present research, BIO and FIV are calculated in the same year. It is in line with previous research IOP Publishing doi:10.1088/1755-1315/1297/1/012069 7 [8], [16], [19], [22]. In Alfarisyi et al [15], the BIO from the previous year matches the FIV this year.…”
Section: Hypotheses Testingsupporting
confidence: 89%
“…A study in the Spanish context found that there is no evidence of higher volatility or material variations in earnings or revenues [14] or the calculation of future cash flow [18] between farmers valuing their biological assets at fair value and those valuing them at historical cost. On the contrary, a study in European Union countries by Bispo and Lopes [16], in 27 countries by Goncalves et al [8], in Malaysia by Kadri et al [19], in Brazilian companies by Silva Filho et al [17], and in Taipei [20] confirms similar results that measuring biological assets at fair value enhances firm value.…”
Section: Introductionmentioning
confidence: 92%